La Impresión 3D como Alternativa de Construcción de Vivienda en Bucaramanga, Santander - Blanco Prada, Geyli Yureli (Universidad Antonio Nariño, 2024)
13 Abstract This research focuses on the study of additive manufacturing, or 3D printing, in the construction industry in order to develop a technical study that shows it as a sustainable alternative for housing construction in Bucaramanga, Santander; This is done through the study of research and projects carried out worldwide that allow us to understand its operation to evaluate its viability in social technical-constructive, environmental, structural, time and cost aspects